Content and Design of Integrity Systems: Evaluating Integrity Systems in Local Government. (4th March 2023) - Hoekstra, Alain; Huberts, Leo; van Montfort, André
Abstract: Public integrity is crucial, especially for local government organizations. Although research points out that a systematic integrity approach is to be preferred, only limited knowledge is available about what such an approach should entail. This article presents a framework that contains seven theory-based elements constituting a complete integrity system. This framework is used to assess the integrity systems in three large European cities, to detect shortcomings of these systems, and to provide recommendations for both administrative practise and future research. Based on the research findings the studied cities are, for instance, recommended: to improve their long-term awareness and support for organizational integrity; to work with a clearer definition of (and vision on) integrity (management); and to reflect more critical on their integrity system based on thorough policy analyzes and evaluations.